Autologous fat grafting: use of closed syringe microcannula system for enhanced autologous structural grafting - Alexander RW; Harrell DB (Dove Medical Press, 2013)
Robert W Alexander,1 David Harrell2 1Department of Surgery, School of Medicine and Dentistry, University of Washington, Seattle, WA, USA; 2Harvest-Terumo Inc, Plymouth, MA, USA Objectives: Provide background for use of acquiring autologous adipose tissue as a tissue graft and source of adult progenitor cells for use in cosmetic plastic surgery. Discuss the background and mechanisms of action of closed syringe vacuum lipoaspiration, with emphasis on accessing adipose-derived mesenchymal/stromal cells and the stromal vascular fraction (SVF) for use in aesthetic, structural reconstruction and regenerative applications. Explain a proven protocol for acquiring high-quality autologous fat grafts (AFG) with use of disposable, microcannula systems. Design: Explain the components and advantage of use of the patented super luer-lock and microcannulas system for use with the closed-syringe system. A sequential explanation of equipment selection for minimally traumatic lipoaspiration in small volumes is presented, including use of blunt injection cannulas to reduce risk of embolism. Results: Thousands of AFG have proven safe and efficacious for lipoaspiration techniques for large and small structural fat grafting procedures. The importance and advantages of gentle harvesting of the adipose tissue complex has become very clear in the past 5 years. The closed-syringe system offers a minimally invasive, gentle system with which to mobilize subdermal fat tissues in a suspension form. Resulting total nuclear counting of undifferentiated cells of the adipose-derived -SVF suggests that the yield achieved is better than use of always-on, constant mechanical pump applied vacuum systems. Conclusion: Use of a closed-syringe lipoaspiration system featuring disposable microcannulas offers a safe and effective means of harvesting small volumes of nonmanipulated adipose tissues and its accompanying progenitor cells within the SVF. Closed syringes and microcannulas are available as safe, sterile, disposable, compact systems for acquiring high-quality AFG. Presented is a detailed, step-by-step, proven protocol for performing quality autologous structural adipose transplantation. Keywords: autologous fat grafting, closed syringe lipoaspiration, adipose-derived adult stem-stromal cell, bioscaffolds, lipoaspiration/liposuction, stromal vascular fraction (SVF)